Hieroglyphs and the afterlife in ancient Egypt - Forman, Werner 1921-2010; Quirke, Stephen (Univ. of Oklahoma Press, 1996)
In ancient Egypt the strategy to achieve life after death relied on hieroglyphs, which united art and writing to help fulfil this ambition. This lavishly illustrated book tells the history of the texts that, through 3,000 years, were designed to ensure survival after death. Egyptologist Stephen Quirke sets out the history of the texts designed to guarantee life beyond death, from the Pyramid Texts for kings and queens, c.2400 BC, to the Book of the Dead used by king and subject alike after 1600 BC. The literature that flourished for millennia met its end under the combined pressures of Greek-speaking government, Roman occupation, and conversion to Christianity. Although Books of the Dead and other funerary manuscripts form the great bulk of surviving Pharaonic texts, no up-to-date survey of this material has been available to a general or scholarly readership. This book, based on a concept by Werner Forman, aims to fill that gap.
Keywords: Pyramidentexte; Totenbuch -- Ägyptisch; Egyptian language -- Writing, Hieroglyphic; Egyptian literature -- History and criticism; Funeral rites and ceremonies -- Egypt; Future life; Kultur; Hieroglyphenschrift; Jenseitsglaube; Geistesgeschichte; Sargtexte; Geschichte; Altägyptisch; Ägypten -- Altertum